Pendekatan Kontekstual dalam Pembelajaran Bahasa Arab untuk Meningkatkan Keterampilan Komunikasi Siswa - Farah Nur Jihan; Zuhrotul Mufidah (Lembaga Penelitian dan Pengabdian Masyarakat Institut Agama Islam Nurul Hakim, 2024)
This study explores the effectiveness of contextual approaches in Arabic language learning to enhance students' communication skills. Utilizing a case study method at a junior high school in city Surabaya, the study involved 30 eighth-grade students and their Arabic language teacher. Data were collected through participatory observation, in-depth interviews, and document analysis. The results indicate that the contextual approach can create a more dynamic and interactive learning environment, increase students' motivation and interest, and improve their communication skills. However, challenges such as limited time, resources, and varying student abilities require additional support from schools and communities. This research makes a significant contribution to the development of language learning theory and practice, emphasizing the importance of sustained support for teachers and the use of technology in contextual learning. Recommendations include continuous training for teachers, differentiated instruction, and community collaboration to enrich the learning context.